Problems of teaching English to high school students from the point of view of teachers in Sabha - Amal Mohameed basher Areedah, (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
The present study aimed to identify the problems facing English language teachers at the secondary stage in the city of Sabha, Libya, from the teachers' perspective. To achieve the study's objectives, the researcher followed the descriptive analytical approach, as it is the most appropriate for the nature of this research. The study population consisted of all English language teachers in secondary schools in Sabha, while the study sample included (40) male and female teachers selected randomly. The researcher developed a questionnaire as a primary tool for data collection, which consisted of several main domains: problems related to the curriculum, problems related to the teacher, and problems related to the student. The validity and reliability of the tool were verified using appropriate statistical methods. After collecting and analyzing the data using the Statistical Package for the Social Sciences (SPSS), the study reached several significant results. The findings indicated that there are statistically significant differences in the problems of teaching English from the teachers' perspective attributed to the gender variable, with these differences favoring males. On the other hand, the results showed that there are no statistically significant differences in the problems related to the curriculum, the teacher, or the student attributed to the variable of years of experience. Furthermore, the study revealed that there are no statistically significant differences in these problems attributed to the scientific qualification variable. Based on these results, the study recommended the necessity of providing modern educational aids and language laboratories in schools, as well as holding training workshops for teachers to keep pace with modern teaching methods and focus on communicative skills rather than just rote memorization for exams.
Keywords: Teaching Problems; English Language; Secondary Stage; Teachers' Perspective; Sabha City